Examining Factors Associated with Stalking-Related Fears Among Men and Women Stalked by Male and Female Acquaintances. Issue 9 (May 2022) - Logan, TK
This study examines experiences of acquaintance stalking victims ( n = 389), recruited from a community sample, by victim and stalker gender and explores factors associated with three measures of fear (fear of harm, perceived capability of stalker to harm, and fear of significant life impact). There were five main findings from this study: (a) although research suggests ex-partner stalkers are the most threatening, assaultive, and harassing stalkers, particularly for women, this study shows that a significant number of acquaintance stalking victims experience high levels of fear, threats, life interference, and assault; (b) women had higher stalking-related fear levels and a greater belief that their stalker was capable of harming them regardless of stalker gender, while men stalked by females were least concerned about harm; (c) close to one-quarter of victims had one unknown background factor and one-third indicated not knowing about two or more background factors suggesting variation in the level of victim knowledge about acquaintance stalkers; (d) the number of threats, stalker history of violence to others, the belief that the stalker does not care about severe consequences, and a greater number of unknown stalker background factors were associated with higher stalking-related fear levels and an increased perception that the stalker was capable of harm; and, (e) higher concern about a significant life impact from the stalking was associated with forced confrontations, believing the stalker wanted revenge, victim vulnerability, proxy stalking, and technology facilitated stalking. Future research is needed to better understand the dynamics of acquaintance stalking, particularly with regard to how close or distant the stalker was to the victim. Considering victim and stalker gender dynamics in acquaintance stalking may be important for safety planning and risk assessment.